Cubic boron nitride: a new prospective material for ultracold neutron application - Sobolev, Yu. G.; Lauer, Thorsten; Borisov, Yu.; Daum, M.; du Fresne, N.; Goeltl, L.; Hampel, G.; Heil, W.; Knecht, A.; Keunecke, M.; Kratz, Jens-Volker; Lang, T.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2010)
At the ultracold neutron (UCN) source of the TRIGA research reactor in Mainz, we have measured for the first time the material optical wall-potential of cubic boron nitride. The measurements were performed with a time-of-flight (TOF) spectrometer. The samples investigated had a wall-potential of (305±15)neV. This value is in good agreement with the result extracted from neutron reflectometry data and theoretical expectations. Because of its high critical velocity for UCN and its good dielectric characteristics, cubic boron nitride coatings (isotopically enriched) will be useful for a number of applications in UCN experiments.